2022
DOI: 10.1002/cbdv.202200864
|View full text |Cite
|
Sign up to set email alerts
|

Myrciaria Genus: Bioactive Compounds and Biological Activities

Abstract: The Myrtaceae family is of angiosperms, imposing its size and economic, cultural, and scientific importance. The genus Myrciaria, belonging to this family, has 33 species currently accepted, many of which are research targets aimed at elucidating their bioactive compounds and biological activities. Most species of the Myrciaria genus have terpenes in their composition, mainly mono and sesquiterpenes, and phenolic compounds such as tannins, phenolic acids, and flavonoids. Other secondary metabolites are also ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
(183 reference statements)
0
3
0
Order By: Relevance
“…Phenolics are a class of plant secondary metabolites often present in species of the genus Myrciaria and with several biological activities well described in the literature, ranging from anticancer activity to anti-inflammatory, antimicrobial, and antioxidant activity, for example. [35,15] Through the cell viability test by MTT using HeLa and NIH/ 3T3 cell lines, it was possible to notice the antiproliferative activity of MGD and MGA. From the IC 50 values for both cell lines, it was possible to calculate the selectivity index of the samples.…”
Section: Analysis Of Cell Cycle Arrest By Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolics are a class of plant secondary metabolites often present in species of the genus Myrciaria and with several biological activities well described in the literature, ranging from anticancer activity to anti-inflammatory, antimicrobial, and antioxidant activity, for example. [35,15] Through the cell viability test by MTT using HeLa and NIH/ 3T3 cell lines, it was possible to notice the antiproliferative activity of MGD and MGA. From the IC 50 values for both cell lines, it was possible to calculate the selectivity index of the samples.…”
Section: Analysis Of Cell Cycle Arrest By Flow Cytometrymentioning
confidence: 99%
“…[8,9,10,11] In recent years, the pharmacological potencial of the Myrtaceae family has been exploring, but the studies are still initial, and some species have demonstrated the anticancer potential as Eugenia pyriformis, Campomanesia adamantium, Myrciaria dubia, Myrciaria plinioides, Myrciaria strigipes. [12,13,14,15] Among the rare reports in the literature about the anticancer potential, of the genus Myrciaria it was chosen to be the target of this work. Myrciaria being native to Brazil and widely distributed in the Brazilian territory and present in the biomes: Caatinga, Cerrado, Amazon, Atlantic Forest, and the Pampas.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of green chemistry, the nitrogen heterocycles with biological activities, such as purine [25] and pyrimidine compounds, [26] are a kind of biological substances, which are the non-toxic and harmless green raw materials. [27,28] By modifying cyclodextrin, biochemical modified cyclodextrin derivatives with excellent performance can be prepared, [29] which can be used as green organic reaction catalysts with excellent performance in aqueous phase. [30] Herein, a recyclable water-soluble palladium catalyst containing thymine ligands derived from cyclodextrin (Thy-CD) was designed for the Suzuki reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%